2018
DOI: 10.22159/ajpcr.2018.v11s1.26560
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Alkaloid Fractions of Zanthoxylum Acanthopodium Dc. Fruits With 1,1-Diphenyl-2-Picrylhydrazyl Assay

Abstract: Objective: Antioxidants are vital substances which possess the ability to protect the body from damage caused by free radical-induced oxidative stress. The purpose of this study is to determine antioxidant activities of alkaloid fractions of Zanthoxylum acanthopodium DC. fruits.Methods: Z. acanthopodium DC. fruit was extracted by maceration. Ethanol extract was fractionated with liquid-liquid extraction using n-hexane and chloroform at pH 3, 7, 9, and 11 to obtained alkaloid fractions. Antioxidant activity for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
(14 reference statements)
0
5
0
1
Order By: Relevance
“…The reports has shown that alkaloids extracts of Euphorbia granulate leaf was shown a great antiradical activity by the characterization of several substances which inhibit free radical DPPH [22]. Further, Rosidah et al, [26] have reported that alkaloid fractions of Z. acanthopodium DC. fruit have very strong antioxidant potential by DPPH method.…”
Section: Discussionmentioning
confidence: 99%
“…The reports has shown that alkaloids extracts of Euphorbia granulate leaf was shown a great antiradical activity by the characterization of several substances which inhibit free radical DPPH [22]. Further, Rosidah et al, [26] have reported that alkaloid fractions of Z. acanthopodium DC. fruit have very strong antioxidant potential by DPPH method.…”
Section: Discussionmentioning
confidence: 99%
“…(1 kg) were repeatedly macerated with ethanol 96% (3 x 3 d, 7.5 L), The filtrate was evaporated to give a viscous extract. Viscous extract was fractionated with n-hexane and continue with chloroform at pH 3,7 and 9 [10], [11], [12].…”
Section: Methodsmentioning
confidence: 99%
“…The total phenol concentration (TPC) of the sample was determined using a Folin ciocalteu technique with gallic acid as a standard [15,16,18].…”
Section: Determination Of Total Phenol Concentrationmentioning
confidence: 99%